Laba: Ketidakstabilan Makna - Sulis Rochayatun; Fitriya Andriyani (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
The purpose of this study is to find out how accountants and non-accountants interpret earnings, and what the reality behind the interpretation. Reality in the accounting profession and students of SMK Akuntansi establish a perception that profit is matching between income and expense (syntactic). Profit is a form of cash proceeds, an increase in economic capability, and a representation of company performance (semantics). Profit is also considered an indicator of corporate success and a tool for controlling management (pragmatics). The results of this study indicate that profit has the meaning of denotation and connotation. Profit not only contains elements of materialism, not only as a form of capitalism, naum profit also contains elements of humanism. The reality of accountants results in the perception that profit is the matching between income and expense. In contrast to these conditions, the reality of non-accountant actually shows more aspects of humanism. These perceptions all have their own truths. This is because the reality that the informants refer to is also different. Thus we know that the meaning of the profit "text" is unstable. Keywords: Earnings, Profit, Unstable, Perception